Method for producing hydrophilic quantum dot

JP2025000159APending Publication Date: 2025-01-07SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023099851
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Benefits of technology

【0023】 以上のように、本発明の親水性量子ドットの製造方法によれば、親水化処理において量子ドットの特性を劣化させることなく親水化できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000159000001_ABST
    Figure 2025000159000001_ABST
Patent Text Reader

Abstract

To provide a method for producing hydrophilic quantum dots that enables hydrophilization without compromising the characteristics of quantum dots during the hydrophilization process.SOLUTION: The present invention provides a method for producing hydrophilic quantum dots, wherein the method involves adding a metal halide, two or more phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to hydrophobic quantum dots dispersed in a nonpolar solvent and heating them to hydrophilize the hydrophobic quantum dots.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing hydrophilic quantum dots. [Background technology]

[0002] Semiconductor crystal particles with nano-sized particle diameters are called quantum dots, and the energy levels of the semiconductor crystal particles become discrete because the excitons generated by light absorption are confined in nano-sized regions, and the band gap changes depending on the particle diameter. Due to these effects, the fluorescent emission of quantum dots is brighter, more efficient, and sharper than that of general phosphors.

[0003] In addition, quantum dots have the characteristic that the band gap changes depending on the particle size, making it possible to control the emission wavelength, and they are expected to be used as wavelength conversion materials in solid-state lighting and displays. For example, using quantum dots as a wavelength conversion material in a display can achieve a wider color gamut and lower power consumption than conventional phosphor materials.

[0004] As a mounting method when using quantum dots as a wavelength conversion material, a method has been proposed in which the quantum dots are dispersed in a resin material, and the resin material containing the quantum dots is laminated with a transparent film to incorporate it into a backlight unit as a wavelength conversion film (Patent Document 1).

[0005] It has also been proposed that quantum dots can be used as a color filter material, allowing the quantum dots to absorb the monochromatic blue light from a backlight unit and emit red or green light, thereby functioning as a color filter and wavelength conversion material, thereby making it applicable to image elements with high efficiency and excellent color reproducibility (Patent Document 2).

[0006] For such applications, quantum dots are generally mixed with photocurable, thermosetting, or thermoplastic polymers or monomers that polymerize with light or heat to form films or color filters, and the compatibility of quantum dots with these polymers or monomers is important because it affects their stability and properties. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2013-544018 [Patent Document 2] JP 2017-21322 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the surface of quantum dots is hydrophobic because it contains ligands such as thiols, carboxylic acids, and amines with long-chain alkyl groups. On the other hand, photopolymerizable and thermally polymerizable polymers and monomers have polymerizable functional groups such as acrylic and epoxy groups, and because they have polarity, they are poorly compatible with quantum dots, causing problems such as aggregation and reduced stability of quantum dots. To solve these problems, hydrophilization treatments are performed on quantum dots.

[0009] Methods being considered for hydrophilizing quantum dots include micellization using amphiphilic surfactants, formation of metal oxide layers such as silica, and introduction of polar functional groups using silane coupling agents. However, each of these treatments involves the detachment of ligands already present on the quantum dot surface, which can result in deterioration of luminescence and reduced stability.

[0010] The present invention has been made to solve the above problems, and aims to provide a method for producing hydrophilic quantum dots that can be hydrophilized without deteriorating the properties of the quantum dots during hydrophilization treatment. [Means for solving the problem]

[0011] The present invention has been made to achieve the above-mentioned object, and provides a method for producing hydrophilic quantum dots, which is characterized in that hydrophobic quantum dots dispersed in a non-polar solvent are hydrophilized by adding a metal halide, two or more types of phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to the hydrophobic quantum dots and heating the hydrophobic quantum dots.

[0012] According to such a method for producing hydrophilic quantum dots, the quantum dots can be made hydrophilic without deteriorating their properties during the hydrophilization treatment.

[0013] In this case, the metal halide that can be used is a chloride, bromide, or iodide of zinc, gallium, indium, cadmium, silver, copper, aluminum, zirconium, titanium, magnesium, manganese, germanium, or lead.

[0014] This is advantageous in suppressing deterioration of the quantum dot properties during the hydrophilization treatment.

[0015] In this case, as the phosphorus compound, any two or more of tributylphosphine, dibutylphenylphosphine, trihexylphosphine, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, diphenylpropylphosphine, methyldiphenylphosphine, isopropyldiphenylphosphine, tri(m-tolyl)phosphine, tri(p-tolyl)phosphine, diphenylpropylphosphine, cyclohexyldiphenylphosphine, and 4-(diphenylphosphino)benzoic acid can be used.

[0016] This is advantageous in carrying out the hydrophilization treatment.

[0017] In this case, as the organic acid having a thiol group or the alcohol having a thiol group, any one of mercaptosuccinic acid, 3-mercaptoisobutyric acid, thiolactic acid, 3-mercaptopropionic acid, mercaptoundecanoic acid, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, 2-mercaptoethanol, 3-hydroxybenzenethiol, 4-hydroxybenzenethiol, mercaptobutanol, mercaptopropanol, 6-mercaptohexanol, 2,3-dimercapto-1-propanol, and 1-thioglycerol can be used.

[0018] This is advantageous in that the quantum dots can be made hydrophilic without deteriorating their properties during hydrophilization treatment.

[0019] In this case, the aprotic polar solvent may be any one of N,N-dimethylformamide, acetonitrile, dimethylsulfoxide, dimethylacetamide, and N-methylpyrrolidone.

[0020] This is advantageous in that the quantum dots can be made hydrophilic without deteriorating their properties during hydrophilization treatment.

[0021] In this case, the quantum yield of the quantum dots after the hydrophilization treatment can be higher than that before the hydrophilization treatment.

[0022] In this way, the method for producing hydrophilic quantum dots according to the present invention makes it possible to improve the quantum yield of the quantum dots after the hydrophilization treatment compared to before the hydrophilization treatment. Effect of the Invention

[0023] As described above, according to the method for producing hydrophilic quantum dots of the present invention, the quantum dots can be hydrophilized without deteriorating their properties during the hydrophilization treatment. [Brief description of the drawings]

[0024] [Figure 1]FIG. 2 shows a flow diagram of a method for producing hydrophilic quantum dots according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below, but the present invention is not limited thereto.

[0026] As described above, there has been a demand for a method for producing hydrophilic quantum dots that can be hydrophilized without deteriorating the properties of the quantum dots in the hydrophilization treatment.

[0027] As a result of intensive research into the above-mentioned problems, the inventors have discovered that a method for producing hydrophilic quantum dots, which comprises adding a metal halide, two or more types of phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to hydrophobic quantum dots dispersed in a non-polar solvent, and heating the hydrophobic quantum dots, can hydrophilize the quantum dots without degrading their properties during the hydrophilization treatment, and have completed the present invention.

[0028] Hereinafter, a method for producing hydrophilic quantum dots according to an embodiment of the present invention, specifically a method for producing hydrophilic quantum dots that are soluble in a polar solvent, will be described with reference to FIG.

[0029] First, hydrophobic quantum dots dispersed in a nonpolar solvent are prepared (S1 in Figure 1).

[0030] In the present invention, the composition and manufacturing method of the hydrophobic quantum dots are not particularly limited as long as they are hydrophobic, and quantum dots can be selected according to the purpose. Examples of the composition of the quantum dots include II-IV group semiconductors, III-V group semiconductors, II-VI group semiconductors, I-III-VI group semiconductors, II-IV-V group semiconductors, IV group semiconductors, perovskite type semiconductors, etc.

[0031] Furthermore, the quantum dots may have only a core or a core-shell structure.

[0032] Specific examples of core materials include CdSe, CdS, CdTe, InP, InAs, InSb, AlP, AlAs, AlSb, ZnSe, ZnS, ZnTe, Zn3P2, GaP, GaAs, GaSb, CuInSe2, CuInS2, CuInTe2, CuGaSe2, CuGaS2, CuGaTe2, CuAlSe2, CuAlS2, CuAlTe2, AgInSe2, AgInS2, AgInTe, AgGaSe2, AgGaS2, AgGaTe2, PbSe, PbS, PbTe, Si, Ge, graphene, CsPbCl3, CsPbBr3, CsPbI3, CH3NH3PbCl3, and mixed crystals and those with dopants added.

[0033] Examples of shell materials include ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, AlSb, BeS, BeSe, BeTe, MgS, MgSe, MgTe, PbS, PbSe, PbTe, SnS, SnSe, SnTe, CuF, CuCl, CuBr, CuI, and mixed crystals of these.

[0034] Furthermore, the quantum dots may be spherical, cubic, or rod-shaped, and the shape of the quantum dots is not limited and can be freely selected. The particle size of the quantum dots can be appropriately selected according to the desired wavelength range, but the average particle size is preferably 20 nm or less, which ensures the quantum size effect, improves the luminous efficiency, and makes it easy to control the band gap by the particle size.

[0035] The particle size of the quantum dots can be calculated from the average of the maximum diameters in a specific direction, i.e., the Feret diameters, of 20 or more particles measured by a particle image obtained by a transmission electron microscope (TEM). Of course, the method for measuring the average particle size is not limited to this, and other methods can be used.

[0036] Ligands may be present on the surface of the quantum dots, and examples thereof include oleic acid, stearic acid, palmitic acid, myristic acid, lauric acid, decanoic acid, octanoic acid, oleylamine, stearyl (octadecyl)amine, dodecyl (lauryl)amine, decylamine, octylamine, octadecanethiol, hexadecanethiol, tetradecanethiol, dodecanethiol, decanethiol, octanethiol, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, tributylphosphine, and tributylphosphine oxide.

[0037] The non-polar solvent is not particularly limited and can be freely selected as long as it has good dispersibility of the quantum dots. As the non-polar solvent, a solvent that is not miscible with the aprotic polar solvent is preferable. Examples of the non-polar solvent include hexane, cyclohexane, pentane, toluene, heptane, and 1-octadecene.

[0038] Next, a metal halide, two or more types of phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent are added to the hydrophobic quantum dots dispersed in a nonpolar solvent, and the mixture is heated to perform a hydrophilization process on the hydrophobic quantum dots (S2 in Figure 1).

[0039] The metal halide is not particularly limited, but a metal halide that matches the composition of the quantum dot is preferred. For example, for InP / ZnS core-shell quantum dots, zinc or indium halides are preferably used. The halogen species is not particularly limited, but chloride, bromide, or iodide are preferred.

[0040] Specific examples of metal halides that can be used include chlorides, bromides, and iodides of zinc, gallium, indium, cadmium, silver, copper, aluminum, zirconium, titanium, magnesium, manganese, germanium, and lead.

[0041] The amount of metal halide added is preferably 2 or more, particularly preferably 5 or more, in terms of weight ratio, relative to the quantum dots being 1.

[0042] The combination and mixing ratio of two or more phosphorus compounds can be freely selected, and can be appropriately selected depending on the type of quantum dots and the type and combination of phosphorus compounds. If only one type of phosphorus compound is used, hydrophilization will be insufficient. Coordination to quantum dots is more likely to occur when the steric hindrance of the ligand is smaller, but when the steric hindrance is smaller, quantum dots are more likely to aggregate with each other. When aggregation occurs, the exchange of existing ligands only occurs partially, and hydrophilization does not progress. Therefore, by combining two types of phosphorus compounds, the existing ligands on the quantum dot surface are replaced with phosphorus compounds with high coordination properties, and further by exchanging the phosphorus compounds with low coordination properties and high steric hindrance for phosphorus compounds with high coordination properties, the aggregation of quantum dots can be suppressed and the exchange of ligands on the quantum dot surface can be efficiently promoted. The phosphorus compound preferably includes two or more selected from tributylphosphine, dibutylphenylphosphine, trihexylphosphine, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, diphenylpropylphosphine, methyldiphenylphosphine, isopropyldiphenylphosphine, tri(m-tolyl)phosphine, tri(p-tolyl)phosphine, diphenylpropylphosphine, cyclohexyldiphenylphosphine, and 4-(diphenylphosphino)benzoic acid.

[0043] The amount of the phosphorus compound added is preferably 5 or more, particularly preferably 10 or more, in terms of weight ratio, relative to the quantum dots being 1.

[0044] As the organic acid having a thiol group or the alcohol having a thiol group, mercaptosuccinic acid, 3-mercaptoisobutyric acid, thiolactic acid, 3-mercaptopropionic acid, mercaptoundecanoic acid, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, 2-mercaptoethanol, 3-hydroxybenzenethiol, 4-hydroxybenzenethiol, mercaptobutanol, mercaptopropanol, 6-mercaptohexanol, 2,3-dimercapto-1-propanol, and 1-thioglycerol are preferably used.

[0045] The amount of organic acid having a thiol group or alcohol having a thiol group added is preferably 10 or more, particularly preferably 20 or more, in terms of weight ratio, assuming that the quantum dots are 1. The organic acid having a thiol group or alcohol having a thiol group can be freely selected, and can be appropriately selected depending on the type of quantum dots and the type and combination of phosphorus compounds to be added.

[0046] The aprotic polar solvent is preferably a solvent that is not miscible with a nonpolar solvent, and N,N-dimethylformamide, acetonitrile, dimethylsulfoxide, dimethylacetamide, and N-methylpyrrolidone are preferably used. The amount of the aprotic polar solvent added can be freely selected and can be appropriately selected according to the desired concentration of quantum dots after the hydrophilization treatment.

[0047] In this way, the method for producing hydrophilic quantum dots is to add a metal halide, two or more phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to the hydrophobic quantum dots dispersed in a nonpolar solvent, and heat the mixture to hydrophilize the quantum dots, and the quantum dots are extracted from the nonpolar solvent into the aprotic polar solvent. The heating temperature is preferably 50° C. or higher, and more preferably 100° C. or higher and lower than the boiling point of the solvent. The heating time may be the time required for the quantum dots to be extracted from the nonpolar solvent into the aprotic polar solvent, for example, about 60 minutes.

[0048] In addition, the quantum yield of the quantum dots after the hydrophilization treatment, such as the internal quantum efficiency, can be higher than that before the hydrophilization treatment. The method for producing hydrophilic quantum dots according to the present invention can improve the quantum yield of the quantum dots after the hydrophilization treatment compared to that before the hydrophilization treatment. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples and comparative examples of the present invention, but the present invention is not limited to these. In this embodiment and the comparative example, core-shell quantum dots of InP / ZnSe / ZnS were used as the quantum dot material.

[0050] (Quantum dot core synthesis process) 0.23g (0.9mmol) of palmitic acid, 0.088g (0.3mmol) of indium acetate, and 10mL of 1-octadecene were placed in a flask, heated to 100℃ under reduced pressure, and stirred to dissolve the raw materials while degassing for 1 hour. After that, nitrogen was purged into the flask, and 0.75mL (0.15mmol) of a solution adjusted to 0.2M by mixing tristrimethylsilylphosphine with trioctylphosphine was added, and the temperature was raised to 300℃. It was confirmed that the solution turned from yellow to red and core particles were formed.

[0051] (Quantum dot shell layer synthesis process) Next, 2.85 g (4.5 mmol) of zinc stearate and 15 mL of 1-octadecene were added to a separate flask, and the mixture was heated to 100°C under reduced pressure and stirred. The mixture was dissolved and degassed for 1 hour to prepare a 0.3 M zinc stearate octadecene solution. 3.0 mL (0.9 mmol) of the solution was added to the reaction solution after core synthesis and cooled to 200°C.

[0052] Next, 0.474 g (6 mmol) of selenium and 4 mL of trioctylphosphine were added to another flask and dissolved by heating to 150°C to prepare a 1.5 M selenium trioctylphosphine solution. The reaction solution after the core synthesis step, which had been cooled to 200°C, was heated to 320°C over 30 minutes while the selenium trioctylphosphine solution was added in 0.1 mL increments to a total of 0.6 mL (0.9 mmol), and the solution was maintained at 320°C for 10 minutes and then cooled to room temperature.

[0053] Then, 0.44 g (2.2 mmol) of zinc acetate was added, and the mixture was heated to 100°C under reduced pressure and stirred to dissolve. The flask was purged again with nitrogen and heated to 230°C, and 0.98 mL (4 mmol) of 1-dodecanethiol was added and held for 1 hour. The resulting solution was cooled to room temperature to produce a solution containing core-shell quantum dots consisting of InP / ZnSe / ZnS.

[0054] (Quantum dot dispersion process) After the reaction was completed, the mixture was cooled to room temperature, ethanol was added to precipitate the reactants, and the mixture was centrifuged to remove the supernatant. The same purification process was repeated, and the mixture was dispersed in hexane, a non-polar solvent, to obtain a hexane solution in which the quantum dots were dispersed. The concentration of quantum dots in this solution was 1 wt%.

[0055] Using a quantum efficiency measurement system (QE-2100) manufactured by Otsuka Electronics Co., Ltd., the emission wavelength, fluorescence emission half-width, and fluorescence emission efficiency (internal quantum efficiency) of the quantum dots at an excitation wavelength of 450 nm were measured. The emission wavelength was 533 nm, the half-width was 40 nm, and the internal quantum efficiency was 70%.

[0056] Example 1 5 mL of the hexane solution containing the quantum dots was placed in a 50 mL flask, and 0.2 g of triphenylphosphine and 1.0 mL of trioctylphosphine were added and stirred. 0.25 g of zinc bromide and 5 mL of N,N-dimethylformamide were further added while stirring.

[0057] After all the solids were dissolved, 0.4 mL of 3-mercaptopropionic acid was added. After stirring at room temperature for a while, the mixture was heated to 100°C under reflux for 60 minutes. After the reaction, the quantum dots moved from the hexane layer to the N,N-dimethylformamide layer, and hydrophilic quantum dots were obtained.

[0058] The emission wavelength, fluorescence emission half-width, and fluorescence emission efficiency (internal quantum efficiency) of the quantum dots after the hydrophilization treatment were measured under the same conditions as immediately after the quantum dot dispersion process. The emission wavelength was 533 nm, the half-width was 40 nm, and the internal quantum efficiency was 81%.

[0059] Example 2 5 mL of the hexane solution containing the quantum dots was placed in a 50 mL flask, and 0.2 g of isopropyldiphenylphosphine and 1.0 mL of trioctylphosphine were added and stirred. 0.25 g of aluminum chloride and 5 mL of dimethyl sulfoxide were further added while stirring.

[0060] After all the solids were dissolved, 0.4 mL of 6-mercaptohexanol was added. After stirring at room temperature for a while, the mixture was heated to reflux at 100°C for 60 minutes to react. After the reaction, the quantum dots moved from the hexane layer to the dimethyl sulfoxide layer, and hydrophilic quantum dots were obtained.

[0061] The emission wavelength, fluorescence emission half-width, and fluorescence emission efficiency (internal quantum efficiency) of the quantum dots after hydrophilization treatment were measured in the same manner as in Example 1, and the emission wavelength was 533 nm, the half-width was 39 nm, and the internal quantum efficiency was 77%.

[0062] Comparative Example 1 5 mL of the hexane solution in which the quantum dots were dispersed was placed in a 50 mL flask, and 1.0 g of triphenylphosphine was added and stirred. Thus, only one type of phosphorus compound was added in Comparative Example 1. Furthermore, 0.25 g of zinc bromide and 5 mL of N,N-dimethylformamide were added while stirring.

[0063] After all the solids were dissolved, 0.4 mL of 6-mercaptohexanol was added. After stirring at room temperature for a while, the mixture was heated to 100°C under reflux for 60 minutes. After the reaction, most of the quantum dots remained in the hexane layer. Therefore, the quantum dots were not sufficiently hydrophilized.

[0064] Comparative Example 2 5 mL of the hexane solution containing the quantum dots was placed in a 50 mL flask, and 0.25 g of zinc bromide and 5 mL of N,N-dimethylformamide were added. After all the solids were dissolved, 0.4 mL of 3-mercaptopropionic acid was added.

[0065] After stirring at room temperature for a while, the mixture was reacted for 60 minutes while being heated to reflux at 100°C. After the reaction, the quantum dots moved from the hexane layer to the N,N-dimethylamide layer, and hydrophilic quantum dots were obtained. Thus, in Comparative Example 2, the hydrophilic treatment was performed without adding a phosphorus compound.

[0066] The emission wavelength, fluorescence emission half-width, and fluorescence emission efficiency (internal quantum efficiency) of the quantum dots after the hydrophilization treatment were measured in the same manner as in Example 1. The emission wavelength was 536 nm, the half-width was 42 nm, and the internal quantum efficiency was 52%. Therefore, the internal quantum efficiency after the hydrophilization treatment was lower than that before the hydrophilization treatment.

[0067] Comparative Example 3 5 mL of the hexane solution in which the quantum dots were dispersed was placed in a 50 mL flask, and 0.2 g of isopropyldiphenylphosphine and 1.0 mL of trioctylphosphine were added and stirred. 5 mL of dimethyl sulfoxide was further added while stirring.

[0068] After all the solids were dissolved, 0.4 mL of 6-mercaptohexanol was added. After stirring at room temperature for a while, the mixture was heated to 100°C under reflux for 60 minutes to react. After the reaction, the quantum dots moved from the hexane layer to the dimethyl sulfoxide layer, and hydrophilic quantum dots were obtained. Thus, in Comparative Example 3, hydrophilic treatment was performed without adding a metal halide.

[0069] The emission wavelength, fluorescence emission half-width, and fluorescence emission efficiency (internal quantum efficiency) of the quantum dots after the hydrophilization treatment were measured in the same manner as in Example 1. The emission wavelength was 535 nm, the half-width was 45 nm, and the internal quantum efficiency was 43%. Therefore, the internal quantum efficiency after the hydrophilization treatment was lower than that before the hydrophilization treatment.

[0070] Thus, in the comparative examples, the hydrophilization treatment was insufficient (Comparative Example 1), or a decrease in luminescence intensity due to the hydrophilization treatment was confirmed (Comparative Examples 2 and 3). On the other hand, in the examples, the hydrophilization treatment proceeded completely, and the treatment was performed without a decrease in quantum yield due to the hydrophilization treatment.

[0071] As described above, it has been confirmed that by subjecting the hydrophilic quantum dots of the present invention to hydrophilization treatment according to the manufacturing method thereof, the hydrophilization treatment can be performed without deteriorating the luminescence characteristics of the quantum dots.

[0072] The present specification includes the following aspects. [1]: A method for producing hydrophilic quantum dots, comprising the steps of: dispersing hydrophobic quantum dots in a non-polar solvent; adding a metal halide, two or more types of phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to the hydrophobic quantum dots; and heating the hydrophobic quantum dots to hydrophilize them. [2]: The method for producing hydrophilic quantum dots according to [1] above, characterized in that the metal halide is a chloride, bromide, or iodide of zinc, gallium, indium, cadmium, silver, copper, aluminum, zirconium, titanium, magnesium, manganese, germanium, or lead. [3]: The method for producing hydrophilic quantum dots according to the above [1] or [2], characterized in that the phosphorus compound is any two or more of tributylphosphine, dibutylphenylphosphine, trihexylphosphine, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, diphenylpropylphosphine, methyldiphenylphosphine, isopropyldiphenylphosphine, tri(m-tolyl)phosphine, tri(p-tolyl)phosphine, diphenylpropylphosphine, cyclohexyldiphenylphosphine, and 4-(diphenylphosphino)benzoic acid. [4]: A method for producing hydrophilic quantum dots according to any one of [1] to [3] above, characterized in that the organic acid having a thiol group or the alcohol having a thiol group is any one of mercaptosuccinic acid, 3-mercaptoisobutyric acid, thiolactic acid, 3-mercaptopropionic acid, mercaptoundecanoic acid, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, 2-mercaptoethanol, 3-hydroxybenzenethiol, 4-hydroxybenzenethiol, mercaptobutanol, mercaptopropanol, 6-mercaptohexanol, 2,3-dimercapto-1-propanol, and 1-thioglycerol. [5]: The method for producing hydrophilic quantum dots according to any one of [1] to [4] above, characterized in that the aprotic polar solvent is any one of N,N-dimethylformamide, acetonitrile, dimethylsulfoxide, dimethylacetamide, and N-methylpyrrolidone. [6]: The method for producing hydrophilic quantum dots according to any one of [1] to [5] above, wherein the quantum yield of the quantum dots after the hydrophilization treatment is higher than that before the hydrophilization treatment.

[0073] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. A method for producing hydrophilic quantum dots, comprising the steps of: adding a metal halide, two or more phosphorus compounds, an organic acid having a thiol group or an alcohol having a thiol group, and an aprotic polar solvent to hydrophobic quantum dots dispersed in a non-polar solvent; and heating the hydrophobic quantum dots to perform a hydrophilic treatment.

2. 2. The method for producing hydrophilic quantum dots according to claim 1, wherein the metal halide is a chloride, bromide, or iodide of zinc, gallium, indium, cadmium, silver, copper, aluminum, zirconium, titanium, magnesium, manganese, germanium, or lead.

3. The method for producing hydrophilic quantum dots according to claim 1, characterized in that the phosphorus compound is any two or more of tributylphosphine, dibutylphenylphosphine, trihexylphosphine, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, diphenylpropylphosphine, methyldiphenylphosphine, isopropyldiphenylphosphine, tri(m-tolyl)phosphine, tri(p-tolyl)phosphine, diphenylpropylphosphine, cyclohexyldiphenylphosphine, and 4-(diphenylphosphino)benzoic acid.

4. The method for producing hydrophilic quantum dots according to claim 1, characterized in that the organic acid having a thiol group or the alcohol having a thiol group is any one of mercaptosuccinic acid, 3-mercaptoisobutyric acid, thiolactic acid, 3-mercaptopropionic acid, mercaptoundecanoic acid, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, 2-mercaptoethanol, 3-hydroxybenzenethiol, 4-hydroxybenzenethiol, mercaptobutanol, mercaptopropanol, 6-mercaptohexanol, 2,3-dimercapto-1-propanol, and 1-thioglycerol.

5. 2. The method for producing hydrophilic quantum dots according to claim 1, wherein the aprotic polar solvent is any one of N,N-dimethylformamide, acetonitrile, dimethylsulfoxide, dimethylacetamide, and N-methylpyrrolidone.

6. The method for producing hydrophilic quantum dots according to any one of claims 1 to 5, characterized in that the quantum yield of the quantum dots after the hydrophilization treatment is higher than that before the hydrophilization treatment.

Citation Information

Patent Citations

  • Fluoroborate phase transfer method for water dispersion of oil-soluble quantum dots

    CN112724979A

  • Low-temperature synthesis process for nanoparticle

    JP2006143526A

  • Method for producing hydrophilic nanoparticle

    JP2007076975A

  • Hydrophylic quantum dot

    JP2007178239A

  • Water-dispersible quantum dot

    JP2009190976A